(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
The interplay between non-alcoholic fatty liver disease (NAFLD), type 2 diabetes mellitus (T2DM), and cardiovascular diseases (CVD) represents a pressing global health challenge due to their increasing prevalence and synergistic contribution to morbidity and mortality. NAFLD affects approximately 25-37% of the global population, with a significantly higher prevalence of 55-70% in individuals with T2DM, making it a critical comorbidity in this group. Both conditions are closely linked to metabolic syndrome, characterized by insulin resistance, dyslipidemia, and chronic low-grade inflammation, which collectively amplify the risk of CVD, the leading cause of death in T2DM patients. NAFLD is now recognized as an independent risk factor for CVD, with evidence suggesting that advanced liver fibrosis exacerbates cardiovascular outcomes. In regions like Uzbekistan, where obesity and T2DM rates are rising due to lifestyle changes and urbanization, the burden of NAFLD and its cardiovascular complications is becoming a public health priority. This research is highly relevant as it addresses the urgent need to understand the pathophysiological mechanisms linking these conditions and to develop integrated diagnostic and preventive strategies to reduce cardiometabolic morbidity. Furthermore, the study aims to contribute to global and regional efforts in improving early detection and management of NAFLD in T2DM patients, potentially reducing healthcare costs and improving quality of life.